Botanical Gardens, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
The postcard shows a path lined with palm trees located in the Government Gardens (Botanical Gardens) in Port of Spain, Trinidad. Postcard No.35.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Palms--Trinidad and Tobago; Plants--Trinidad and Tobago; Gardens--Trinidad and Tobago